2018
DOI: 10.21037/tgh.2018.10.10
|View full text |Cite
|
Sign up to set email alerts
|

A review of endoscopic ultrasound guided endoscopic retrograde cholangiopancreatography techniques in patients with surgically altered anatomy

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) is the primary therapeutic intervention for pancreaticobiliary duct diseases. Surgically altered anatomy (SAA) makes performing successful ERCP challenging. In this review article the concept of endoscopic ultrasound guided pancreaticobiliary drainage (EUS-PBD) in cases of SAA where conventional ERCP fails or is not possible will be reviewed. EUS-PBD serves as an emerging and promising alternative for pancreaticobiliary therapy in the hands of skilled endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(53 reference statements)
0
7
0
1
Order By: Relevance
“…Three major techniques are available for drainage via the IHBD: transmural biliary stenting, antegrade biliary stenting, and the rendezvous technique. 7,41 Because the rendezvous technique requires endoscopic access to the papilla or anastomosis, transmural or antegrade biliary stenting is preferentially performed for SAA patients. Although little information exists on whether transmural or antegrade stenting is more appropriate, our previous study showed that transmural stenting combined with antegrade stenting contributed to long stent patency.…”
Section: Discussionmentioning
confidence: 99%
“…Three major techniques are available for drainage via the IHBD: transmural biliary stenting, antegrade biliary stenting, and the rendezvous technique. 7,41 Because the rendezvous technique requires endoscopic access to the papilla or anastomosis, transmural or antegrade biliary stenting is preferentially performed for SAA patients. Although little information exists on whether transmural or antegrade stenting is more appropriate, our previous study showed that transmural stenting combined with antegrade stenting contributed to long stent patency.…”
Section: Discussionmentioning
confidence: 99%
“…Ведение пациентов с послеоперационно изменённой анатомией является реально существующей проблемой, связанной с возрастанием количества пациентов, подвергшихся бариатрической хирургии, а также операциям по поводу как доброкачественных, так и злокачественных поражений верхних отделов ЖКТ или панкреато-билиарной зоны, включая резекцию желудка по Бильрот-2 или панкреатодуоденальную резекцию [1] Известны сообщения о технических трудностях панкреатобилиарной эндоскопии у пациентов при резекции желудка по Бильрот-2, когда исследование головки поджелудочной железы и холедоха сопряжено с трудной интубацией приводящей петли вследствие выраженного изгиба, фиксации кишки, изменённой анатомией [2,3]. В случае безуспешной ЭРПХГ может применяться ЧЧХГ с дренированием, которая также имеет свои ограничения и осложнения [4].…”
Section: Discussionunclassified
“…The complication rate of the procedure has been reported to reach 20% and the steep learning curve associated with the procedure may be problematic. [6][7][8] Percutaneous transhepatic biliary drainage (PTBD) is an established technique that may be indicated in cases of previously failed ERCP, particularly in those involving a surgically altered anatomy. 9,10 However, the specimen adequacy and diagnostic sensitivity of tissue obtained through PTBD may be unsatisfactory, and bile duct stone clearance with PTBD alone can be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The complication rate of the procedure has been reported to reach 20% and the steep learning curve associated with the procedure may be problematic. 6 - 8 …”
Section: Introductionmentioning
confidence: 99%